Congenital absence of the left thumb in a surviving twin - a genetic disorder - D N Sinha (Wolters Kluwer Medknow Publications, 2014)
Congenital absence of left thumb with deformities of carpal bones in a twin born adult woman is reported here. The subject is the only surviving twin aged forty years reported to the hospital with a complaint of weakness of left hand. On examination, left hand did not possess the thumb and appeared to be less muscular. A single prominent crease like Simian crease was noticed on the left palm without other features of Down's syndrome. No radial pulse was palpable on the left side at its usual position on the wrist. Associated developmental anomalies of carpal bones and radius on left side were noted in radiograph: Scaphoid and lunate were shortened. Trapezoid was absent. Metacarpals were shorter and lower end of the radius was less expanded when compared to right side. Genetic disorders associated with twin pregnancy might have resulted in the absence of left thumb. Orthopaedic surgeons should be aware of these associations to avoid complications during surgery.